2008
DOI: 10.1103/physrevlett.100.117004
|View full text |Cite
|
Sign up to set email alerts
|

Two-Mode Variational Monte Carlo Study of Quasiparticle Excitations in Cuprate Superconductors

Abstract: Recent measurements of quasiparticles in hole-doped cuprates reveal highly unusual features: 1) the doping-independent Fermi velocity, 2) two energy scales in the quasiparticle spectral function, and 3) a suppression of the low energy spectral weight near the zone center. The underlying mechanism is under hot debate. We addressed these important issues by a novel two-mode variational Monte Carlo (VMC) study of the t-J model. We obtained results in agreement with the experiments but without invoking extrinsic e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Apart from energetics, various other physically interesting properties may be calculated from the projected wave function, such as static or dynamic spin structure factors, excitation gaps, modular matrices, etc. 15,66,[113][114][115][116][117][118][119][120] The invariant gauge group (IGG) is an important concept in the phenomenology of quantum spin liquid phases when we view H 0 as a low-energy effective theory. It is defined as the subgroup of gauge transformations G that leave the spinon Hamiltonian H 0 invariant, i.e., g(u) = u for all g ∈ IGG u .…”
Section: Quadratic Spinon Hamiltoniansmentioning
confidence: 99%
“…Apart from energetics, various other physically interesting properties may be calculated from the projected wave function, such as static or dynamic spin structure factors, excitation gaps, modular matrices, etc. 15,66,[113][114][115][116][117][118][119][120] The invariant gauge group (IGG) is an important concept in the phenomenology of quantum spin liquid phases when we view H 0 as a low-energy effective theory. It is defined as the subgroup of gauge transformations G that leave the spinon Hamiltonian H 0 invariant, i.e., g(u) = u for all g ∈ IGG u .…”
Section: Quadratic Spinon Hamiltoniansmentioning
confidence: 99%
“…Meanwhile, methods of calculating the spin and charge dynamical structure factors utilizing the variational wave functions for ground and excited states have been proposed recently [24][25][26][27][28]. Some attempts have been made to calculate the excitation spectrum on larger clusters of the t-J model [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In order to elucidate the mechanism of the HEK, it is necessary to look into electron-doped HTSCs, too, and to identify the differences and similarities between the hole-and electron-doped HTSCs. Theoretical studies using the t-J model have demonstrated that there is no HEK in the electron-doped HTSCs due to the lack of the incoherent part in the photoemission spectra [18,19], while other theoretical studies have demonstrated that a HEK of the electron-doped HTSCs exists in a high-energy region compared with that of the hole-doped ones due to a charge modulation mechanism [20] or due to the different magnetic susceptibilities of the hole-and electrondoped HTSCs according to a paramagnon-induced HEK mechanism [15]. Since most of the studies of the HEK have been performed in a limited region of momentum space, more systematic investigations of the momentum dependence of the HEK are necessary to understand the origin of the HEK.…”
Section: Introductionmentioning
confidence: 99%